Massive quantities of pelagic sargassum on the shores of san andres island, southwestern caribbean (2015)
We report an unusual biomass of floating Sargassum, composed of the species S. fluitans and S. natans, that reached the northeastern coast of San Andres island in September 2014. The time and size of the event is unprecedented to the island.